Performance and Emissions Analysis of N-Butanol Blended with Gasoline in Spark Ignition Engine - Abdulrahman, A; Adisa, A. B.; Dandakouta, H. (International Journal of Engineering and Management Research, 2018)
The power developed by an internal-combustion engine depends upon the fuel used for combustion. Fuels commonly used in internal combustion engines are derived from crude oil, which are depleting and are important sources of air pollution. In this study, n-butanol was used as an additive with gasoline as fuel in spark ignition engine. N-butanol exhibits good burning characteristics, contain oxygen, reduces some exhaust emissions and as well, has energy density and octane rating close to that of gasoline. The various blend rates (4, 8, 12, 16 and 20 percent by volume) were used in the engine performance analysis using a TD110-115 single cylinder, four-stroke air-cooled spark ignition engine test rig, under different loading conditions. An SV-5Q automobile exhausts gas analyzer was used to measure the concentration of gaseous emissions such as unburnt hydrocarbon (UHC), carbon monoxide (CO), and carbon dioxide (CO2) from the engine tail pipe. The results of engine performance showed reduction in the exhaust temperature was observed for the blends than to that of gasoline. It was observed that all the blends improved the brake thermal efficiency and exhibited high fuel consumption, lower specific energy consumption and lower emissions than gasoline. All the blends performed satisfactorily on spark-ignition engine without engine modification.